Remaja Kristen di Era Digital: Strategi Konseling Menghadapi Krisis Identitas Akibat Media Sosial - Heintje Kobstan; Meily Kouwagam; Lita Patricia Lunanta (PT. Giat Konseling Nusantara, 2026)
This is an analysis of the identity crisis experienced by Christian adolescents within a digital ecology filled with social comparison, cyberbullying, sleep disruption, and Fear of Missing Out (FOMO). The background highlights numerous findings on how social media affects individual well-being. There are real psychosocial dangers, but also opportunities to enhance peer support and faith. The method used is a narrative-integrative review with a qualitative approach to literature from 2010–2025, sourced from academic publishers and databases like Google Scholar, PubMed, and Scopus. Additionally, theoretical synthesis from Erikson–Marcia, DSMM, I-PACE, and integrated Christian counseling practices are utilized. Risk mechanisms (e.g., upward social comparison, FOMO, cyberbullying, and displacement of offline activities) and protective factors (e.g., media literacy, supportive monitoring, faith communities) are discussed. The discussion then shifts to evidence-based intervention strategies, such as metric-based CBT, media literacy and algorithmic awareness, sleep hygiene, forgiveness interventions, and family-school-church digital covenants. The